Pemikiran Teologi Transformatif “Moeslim Abdurrahman” - Irma Nirmala Sartika Nasution (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Transformative theology is Islam that has an orientation and initiates the need for social change for the better. Islam must have a social criticism orientation, not only as enlightenment or as a modernization discourse, but Islam that wants to change so that the situation is more just. Based on the research conducted, it can be seen that, Moeslim Abdurrahman's Theological Characteristics is Transformative Islamic Theology which is a partial action that is able to arm marginalized communities to be able to rise and get out of adversity and poverty that they are currently facing in order to become even better. and Moeslim Abdurrahman's main thoughts about poverty, which are divided into three, namely first, poor in religious knowledge, namely if they want to have a dialogue with God, they must call people who are considered experts to read prayers, second, poor in religious institutions, namely religious organizations that generally controlled by the upper middle class society while the lower class people do not have access to justice, third, poor in terms of socio-political are those who are marginal people who are politically dead, have no voice and have no articulation at all.